The Determinants of Nutritional Awareness of Bedouin' Families in El-Qantara Sharq District, Ismailia Governorate, Egypt - Mohammed Ibrahim; Maher Attia (New Valley Journal of Agricultural Science, 2022)
This research aims to: 1) measure level of respondents’ nutritional awareness in relation to food quality, food safety, and nutrition, 2) identify the relationships between characteristics of respondents and their nutritional awareness; 3) determine factors influencing respondents’ nutritional awareness, and 4) determine constrains facing their awareness and their suggestions to solve it. the village of jalbana was chosen as the nearest village to El-Qantara Sharq district to conduct the empirical study, data were collected through personal interviews using a questionnaire form from a randomly simple sample of 320 respondents during March 2022. Frequencies, percentages, arithmetic mean, and standard deviation, correlation coefficients, and multiple regression test were used for data analysis and presentation. The results showed that level of respondents’ nutritional awareness was low and medium. The results also revealed that there were significant relationships between nutritional awareness and the following eight variables (i.e., the number of years of formal education, number of years of marriage, the total amount spent on food per month, responsible for determining the components of food, the number of cognitive sources, openness to the outside society, cultural openness, attitudes towards the correct eating habits). While the results of multiple regression showed that more than 22%, 12.5%, 7.5%, 5%, 3.1%, 1.9% of the variance in nutritional awareness level are explained by number of sources of knowledge about food awareness, number of years of formal education, responsible for the family's food components, the trend towards correct eating habits, number of years of marriage, and openness to the outside society, respectively.